ASSESSMENT OF PREVALENCE AND IMPACTS OF WORK-RELATED MUSCULOSKELETAL DISORDERS AMONG NURSES AT INTERMEDIATE HOSPITALS IN NAMIBIA - Ananias Akweetelela; Moses Chirimbana; Anna Shilunga; Kabwebwe Honoré Mitonga (Global Journal of Public Health Medicine)
Introduction: Work-related musculoskeletal disorders (WRMSDs) have been ranked as the major cause of disability globally. Namibian intermediate hospital (IH) nurses are overworked and susceptible to musculoskeletal diseases. The study aimed to determine the 12-month prevalence, and impacts of WRMSDs among nurses at IHs Katutura, Onandjokwe, Oshakati, and Rundu in Namibia.